Level, Slope, Curvature of Sovereign Yield Curve and Fiscal Behaviour - António Afonso (2010)
We study fiscal behaviour and the sovereign yield curve in the U.S. and Germany in the period 1981:I-2009:IV. The latent factors, level, slope and curvature, obtained with the Kalman filter, are used in a VAR with macro and fiscal variables, controlling for financial stress conditions. In the U.S., fiscal shocks have generated (i) an immediate response of the short-end of the yield curve, associated with the monetary policy reaction, lasting between 6 and 8 quarters, and (ii) an immediate response of the longendof the yield curve, lasting 3 years, with an implied elasticity of about 80% for the government debt ratio shock and about 48% for the budget balance shock. In Germany, fiscal shocks entail no significant reactions of the latent factors and no response of the monetary policy interest rate. In particular, while (i) budget balance shocks created no response from the yield curve shape, (ii) surprise increases in the debt ratio caused some increase in the short-end and the long-end of the yield curve in the following 2nd and 3rdquarters.